2020
DOI: 10.1007/s13730-020-00447-z
|View full text |Cite
|
Sign up to set email alerts
|

Melanotan II: a possible cause of renal infarction: review of the literature and case report

Abstract: Renal infarction is an uncommon condition resulting from an acute disruption of renal blood flow and it is potentially lifethreatening disease. The cause and outcome of renal infarction is not well established and is frequently misdiagnosed or diagnosed late. Melanotan II is a non-selective melanocortin-receptor agonist and its effect on humans is an increasing of skin pigmentation, producing of spontaneous penile erection and sexual stimulation. Melanotan II inducing rhabdomyolysis and renal failure have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The latter dictates detailed search for hypercogaulable states and offending drugs. The list includes; OCP, Marijuana smoking, Cocaine, anabolic steroids, melanotan, NSAIDs, thrombophilic disorders and even Covid-19 infection [11][12][13][14][15][16][17] . In those reports, enhancement of platelet aggregation, increased thromboxane synthesis and drug-induced endothelial and vasospastic injury were the most plausible mechanisms of infarctions.…”
Section: Discussionmentioning
confidence: 99%
“…The latter dictates detailed search for hypercogaulable states and offending drugs. The list includes; OCP, Marijuana smoking, Cocaine, anabolic steroids, melanotan, NSAIDs, thrombophilic disorders and even Covid-19 infection [11][12][13][14][15][16][17] . In those reports, enhancement of platelet aggregation, increased thromboxane synthesis and drug-induced endothelial and vasospastic injury were the most plausible mechanisms of infarctions.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the general risks of using an unregulated substance, common adverse effects include acne, facial flushing, gastrointestinal tract upset, and sensitivity to sunlight (Table ). 1,9,10 Several case reports have linked melanotan II to cutaneous changes, including dysplastic nevi and even melanoma. 1 Less common complications, such as renal infarction and priapism, also have been observed with melanotan II use.…”
Section: Practice Pointsmentioning
confidence: 99%
“…1 Less common complications, such as renal infarction and priapism, also have been observed with melanotan II use. 9,10 Even with the known risks involving tanning beds and skin cancer, an analysis by Kream et al 11 in 2020 showed that 90% (441/488) of tanning-related videos on TikTok promoted a positive view of tanning. Of these TikTok videos involving pro-tanning trends, 3% (12/441) were specifically about melanotan II nasal spray, injection, or both, which has only become more popular since this study was published.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Secondly, it is possible to chart similar instances of diffusion by examining the growth of melanotan II, a relatively new drug with properties that mimic the effects of exposure to the sun, whilst also reportedly inducing penile erections and increasing sexual desire and weight loss (Hadley and Dorr 2006). While much of the concerns regarding melanotan II has centred around its injection by naïve users (Van Hout and McVeigh 2019), even with the development and promotion of a nasal formulation, there remains evidence of adverse consequences, such as renal infarction and systemic toxicity (Peters, Hadimeri et al 2020) (Nelson, Bryant et al 2013) and most commonly changes to the skin such as the development of melanoma (Paurobally, Jason et al 2011, Hjuler andLorentzen 2014).…”
Section: The Bigger Picture: Enhanced Bodybuilders Innovation and Diffusionmentioning
confidence: 99%